Respuesta :

Ok
2x + y - z = 7
-2y +3z = -15
x + 2y - 5z = 17
combine 2nd 3rd
x - 2z = 2
x = 2z + 2
double first statement
4x + 2y - 2z = 14
combine with second statement
4x + z = -1
substitute 2z + 2 for x
8z + 8 + z = -1
combine like terms
9z + 8 = -1
sub 8 from both sides
9z = -9
divide both sides by 9
z = -1
substitute -1 for z in second statement
-2y - 3 = -15
add 3 to both sides
-2y = -12
divide both sides by -2
y = 6
substitute -1 for z into the fifth statement
x = -2 + 2
x = 0
ACCESS MORE